Implementation of Data-Based Planning for Learning Quality Improvement: A Case Study at SMP Negeri 2 Taman Pemalang - Hansen Lutfiartha; Endang Wuryandini; Muhtarom Muhtarom (Journal of Educational Sciences, 2026)
The transition from administrative to evidence-based school management is essential for enhancing educational outcomes. This study aims to analyze the implementation of Data-Based Planning in formulating annual learning programs at SMP Negeri 2 Taman, Pemalang Regency. Employing a qualitative case study design, data were collected through in-depth interviews, participant observation, and document analysis, including the Education Report Card, Annual Work Plan, and School Activity and Budget Plan. The findings reveal that Data-Based Planning implementation proceeds through three systematic stages: identification, reflection, and improvement. In the identification phase, stakeholders analyzed report card data to prioritize quality issues. The reflection phase utilized collaborative forums, such as Learning Communities and In-House Training, to foster a reflective teacher culture. The improvement phase translated these insights into concrete interventions like Lesson Study and academic coaching. Empirical results show a tangible increase in learning quality scores from 59.57 in 2022 to 67.00 in 2024. The study concludes that Data-Based Planning successfully transforms school planning into an adaptive, evidence-based process. These results imply that participatory instructional leadership and consistent monitoring are critical for establishing a sustainable culture of quality improvement.